The Effects of Positive or Neutral Communication during Acupuncture for Relaxing Effects: A Sham-Controlled Randomized Trial. (11th February 2016) - Rosén, Annelie; Lekander, Mats; Jensen, Karin; Sachs, Lisbeth; Petrovic, Predrag; Ingvar, Martin; Enblom, Anna
Abstract : Introduction . The link between patient-clinician communication and its effect on clinical outcomes is an important clinical issue that is yet to be elucidated. Objective . Investigating if communication type (positive or neutral) about the expected treatment outcome affected (i) participants' expectations and (ii) short-term relaxation effects in response to genuine or sham acupuncture and investigating if expectations were related to outcome. Methods . Healthy volunteers (n = 243, mean age of 42) were randomized to one treatment with genuine or sham acupuncture. Within groups, participants were randomized to positive or neutral communication, regarding expected treatment effects. Visual Analogue Scales (0–100 millimeters) were used to measure treatment expectations and relaxation, directly before and after treatment. Results . Participants in the positive communication group reported higher treatment expectancy, compared to the neutral communication group (md 12 versus 6 mm, p = 0.002 ). There was no difference in relaxation effects between acupuncture groups or between communication groups. Participants with high baseline expectancy perceived greater improvement in relaxation, compared to participants with low baseline levels (md 27 versus 15 mm, p = 0.022 ). Conclusion . Our data highlights the importance of expectations for treatment outcome and demonstrates that expectations can be effectively manipulated using a standardized protocol that in future research may be implemented in clinical trials.